2009
DOI: 10.1097/ico.0b013e31818c9003
|View full text |Cite
|
Sign up to set email alerts
|

Keratoconus Associated With Corneal Stromal Amyloid Deposition Containing TGFBIp

Abstract: Purpose To report the identification and characterization of stromal amyloid deposits in patients with keratoconus. Methods The excised corneal buttons from two patients diagnosed clinically with keratoconus underwent histochemical analysis with Masson trichrome, Congo red, Alcian blue and periodic acid-Schiff stains as well as immunohistochemical analysis for the TGFBI protein product (TGFBIp), prealbumin, lysozyme, kappa and lambda light chain expression. Following the collection of DNA from both patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Previous studies by us1517 and others2542434445 have indicated a link between KC pathophysiology and the TGF-β pathway. In order to determine if Quercetin inhibited terminal myofibroblast differentiation in a TGF-β dependent manner, we investigated changes in the TGF-β pathway.…”
Section: Resultsmentioning
confidence: 90%
“…Previous studies by us1517 and others2542434445 have indicated a link between KC pathophysiology and the TGF-β pathway. In order to determine if Quercetin inhibited terminal myofibroblast differentiation in a TGF-β dependent manner, we investigated changes in the TGF-β pathway.…”
Section: Resultsmentioning
confidence: 90%
“…Recently, potential mutation in TGFBI was identified in Chinese KC patients (36). TGFBIp has been identified in primary amyloid deposits of hereditary corneal dystrophies and in secondary amyloidosis of the cornea of diverse etiologies (37), as well as in corneal stromal amyloid deposits in KC patients (38). Increased levels of TGFBIp have been identified in corneas of patients with Fuchs’ endothelial corneal dystrophy (39, 40).…”
Section: Discussionmentioning
confidence: 99%
“…However, no mutations in the hotspots of the TGFBI gene were found in this case, suggesting that the hyalinosis and amyloidosis were secondary in nature. Secondary amyloidosis has previously been reported in Fuchs endothelial dystrophy8 and a variety of corneal degenerations9, 10, but not in MCD. Taken together, this clinicopathological report is noteworthy as case 1 represents MCD with degenerative hyalinosis and amyloidosis.…”
Section: Discussionmentioning
confidence: 89%